Guidelines for public management : accompanying document and selected case studies - The World Bank.; International Monetary Fund. (Washington, D.C. : World Bank, 2003)
This guidelines are designed to assist policy makers in considering reforms to strengthen the quality of their public debt management and reduce their country vulnerability to domestic and international financial shocks.
Prepared by the Staff of the International Monetary Fund and the World Bank.
osa 06/09/2016
Loans
Keywords: Debt management; Debt management - Public